Private Participation in Health Services - Harding, April; Preker, Alexander S. (Washington, DC: World Bank, 2013)
Private participation in health services is often a controversial issue, although many countries already make use of private services to further aims in health care. The book draws on a wide range of country experience to provide a judicious blend of practical advice and useful information on health services privatization issues. It discuses how to assess the potential for private sector involvement, how to engage in contracting with the private sector for health services, and how to regulate the sector. It also provides advice on what to do when key information is not there: a crucial element of any strategy, especially in developing countries where data and information sources are scarce. With the decline of ideology, politicians have grown increasingly fond of the dictum "What is best is what works." This book is an excellent lesson on what works in health care, or more precisely, on how to make what works work better, especially with respect with to the involvement of the private sector. Only with a good public-private mix can we achieve our goal of improving health care for all.